Physical and Chemical Properties of Nano Zinc Oxide Modified Asphalt Binder - Mohd Yunus , Khairul Nizam; Zainorabidin, Adnan; Mohd Kamaruddin, Nurul Hidayah; Ahmad, Mohd Khairul; Anuar, Nur Fatin Nadiah; Yaakop, Siti Noor Kamariah (International Journal of Integrated Engineering, 2022)
Recently, nanotechnology has been used in all fields of science, including pavement engineering due to promising and improvement of materials offered. The modification of asphalt binder has evolved gradually, with several types of nanomaterials being employed to modify the asphalt binder. In this study, nano zinc oxide with flake structure was used as a modifier in asphalt binder. The nano modifiers were blended with penetration grade 60/70 asphalt binder at 3%, 5%, and 7%, respectively. Physical properties of the modified asphalt binders were then examined, including storage stability, penetration, softening point, and viscosity. Meanwhile, the chemical property was determined using Fourier-Transform Infrared Spectroscopy. It was discovered that 3% nano zinc oxide produced the best results. Nano zinc oxide was found not to show separation at high temperatures in a storage stability test. The addition of nano zinc oxide to the asphalt binder also reduced the penetration, increased the softening point, and reduced the viscosity. The high penetration index value also indicates that the asphalt binder treated with nano zinc oxide is thermally resistant. Keywords: Nanotechnology, asphalt binder, nano zinc oxide, physical properties, chemical properties.